Characteristics of diode temperature sensors which exhibit Mott conduction in low temperature region - Borblik, V.L.; Shwarts, Yu.M.; Shwarts, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Heavily doped silicon diodes of n⁺⁺-p⁺ type which exhibit the Mott
temperature dependence of the forward current in a certain range of bias voltages and
low temperatures have studied from the point of their use as temperature sensors. In the
region of hopping conduction, the operating signal of diodes U (T) (U is a voltage drop
across the diode during the passage of a constant current, T is the temperature)
reproduces the Mott law (with opposite sign in the exponent), and the temperature
sensitivity of such sensors after passing through a minimum (as the temperature is
lowered) increases again up to the values typical of room temperature